Surgical Effects of Resecting Skull Base Tumors Using Pre-operative Multimodal Image Fusion Technology: A Retrospective Study - Jian, Zhi-heng; Li, Jia-yan; Wu, Kai-hua; Li, Yu; Li, Shi-xue; Chen, Hai-dong; Chen, Gang (Frontiers in Neurology, 2022)
Objectives To analyze the surgical effects of resecting skull base tumors using multimodal three-dimensional (3D) image fusion technology in the neurosurgery department and present some typical cases. Methods From October 2019 to October 2021, we included 47 consecutive patients with skull base tumors in the Neurosurgery Department at Zhuhai People's Hospital in this study. Pre-operative head computed tomography and magnetic resonance imaging data acquisition was performed using the GE AW workstation software for registration fusion, image fusion, and 3D reconstruction. The surgical approach and surgical plan were designed based on the multimodal 3D image, and the resection rate, complication rate, and operative time of the surgery using the multimodal image fusion technique were analyzed. Results The reconstructed multimodal 3D images precisely demonstrated the size, location, and shape of the tumor along with the anatomical relationship between the tumor and surrounding structures, which is consistent with the intraoperative findings. Among 47 patients, 39 patients (78.7%) underwent total resection, 5 (14.9%) underwent subtotal resection, and 3 (6.4%) underwent partial resection. The mean operative time was 4.42 ± 1.32 h. No patient died during the inpatient period. Post-operative complications included 6 cases of cerebrospinal fluid leakage (14.9%), 3 cases of intracranial infection (6.4%), 6 cases of facial paralysis (12.8%), 2 cases of dysphagia (4.3%), and 1 case of diplopia (2.1%), all of which were improved after symptomatic treatment. The application value of pre-operative 3D image fusion technology was evaluated as outstanding in 40 cases (85.1%) and valuable in 7 cases (14.9%). Conclusions Pre-operative multimodal image fusion technology can provide valuable visual information in skull base tumor surgery and help neurosurgeons design the surgical incision, choose a more rational surgical approach, and precisely resect the tumor. The multimodal image fusion technique should be strongly recommended for skull base tumor surgery.